Ferroelectricity of trimethylammonium bromide below room temperature. Issue 17 (2nd April 2020) - Gao, Zhangran; Wu, Yuying; Tang, Zheng; Sun, Xiaofan; Yang, Zixin; Cai, Hong-Ling; Wu, X. S.
Abstract : Ferroelectricity of trimethylammonium bromide was discovered near room temperature, which undergoes a first-order paraelectric–ferroelectric phase transition at the Curie temperature around 286 K. Abstract : Ferroelectrics are widely applied in modern industrial production due to their fascinating physical properties. New findings on organic ferroelectric materials have gained the attention of researchers because they have flexible designs and are easy to produce. Here, we report on an overlooked compound, trimethylammonium bromide ((CH3 )3 NHBr), that demonstrates ferroelectricity just below room temperature. The compound undergoes a first-order paraelectric–ferroelectric phase transition at the Curie temperature ( T c ) around 286 K, accompanied by significant changes in the structural, thermal and electrical properties. The space group of the compound transforms from P 21 to P 21 / m at the Curie temperature T c . The remnant polarization P r is about 0.4 μC cm −2 at 230 K and 0.25 μC cm −2 at 243 K. This finding reveals a new pathway to design and synthesize molecular ferroelectrics.